2019
DOI: 10.3390/e21121157
|View full text |Cite
|
Sign up to set email alerts
|

Entropy Generation Assessment for Wall-Bounded Turbulent Shear Flows Based on Reynolds Analogy Assumptions

Abstract: Heat transfer modeling plays a major role in design and optimization of modern and efficient thermal-fluid systems. Further, turbulent flows are thermodynamic processes, and thus, the second law of thermodynamics can be used for critical evaluations of such heat transfer models. However, currently available heat transfer models suffer from a fundamental shortcoming: their development is based on the general notion that accurate prediction of the flow field will guarantee an appropriate prediction of the therma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Moreover, the suitability of entropy generation-based approach in providing a deeper insight about the coupled thermo-fluid flow processes is also reported in our previous works [ 20 , 21 ] using LES-based detailed description. Additionally, such a method has been successfully utilized to investigate various technical configurations and physical processes, as reported in [ 17 , 19 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. More recently, the entropy generation based analysis of monolithic catalytic converter using LES was carried out by Li et al [ 34 ] to understand especially the turbulent flow transition and to characterize the single phase flow inside the SCR monolith, namely the impinging flow with stagnation, re-circulation, flow separation and laminarization.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the suitability of entropy generation-based approach in providing a deeper insight about the coupled thermo-fluid flow processes is also reported in our previous works [ 20 , 21 ] using LES-based detailed description. Additionally, such a method has been successfully utilized to investigate various technical configurations and physical processes, as reported in [ 17 , 19 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. More recently, the entropy generation based analysis of monolithic catalytic converter using LES was carried out by Li et al [ 34 ] to understand especially the turbulent flow transition and to characterize the single phase flow inside the SCR monolith, namely the impinging flow with stagnation, re-circulation, flow separation and laminarization.…”
Section: Introductionmentioning
confidence: 99%
“…A detailed description of entropy generation analysis, in particular in the context of LES, can be found in [21] and elsewhere. Several investigations based on entropy generation for different technical configurations and physical processes have been reported [18,[22][23][24][25][26][27][28][29][30][31][32][33]. However, a study based on the entropy generation analysis for the realistic automobile catalytic converter has not yet been reported.…”
Section: Introductionmentioning
confidence: 99%
“…All of these aforementioned analyses for entropy production in combustion processes were carried out in configurations without the influence of walls. Recent LES analyses [20][21][22] for non-reacting wall-bounded flows with heat transfer revealed that the presence of a wall and the associated boundary layer have significant influence on entropy generation rates. Therefore, it can be expected that the presence of a wall will have a significant influence on the entropy generation rate in premixed flames due to three-way interactions between wall, fluid flow and chemical processes within the boundary layer, but insufficient information is available in the literature for exergy analysis for turbulent premixed FWI.…”
Section: Introductionmentioning
confidence: 99%